The Impact of Neuromarketing on Acquisition Wearable Technology Products: A Survey Study of the Opinions of a Sample of Students at Some of the Forms of the Northern Technical University in Nineveh Governorate (International Journal of Financial, Administrative and Economic Sciences, 2026)
This research aims to analyze the impact of neuromarketing across its main dimensions (sensory awareness, targeted advertising, behavioral flexibility, and product satisfaction) on consumer attitudes toward Acquisition wearable technology products. This research was conducted through a field study of the opinions of a sample of students in various departments at the Northern Technical University in Nineveh Governorate. The study addressed the research question of the extent to which neuromarketing influences student decisions related to purchasing wearable technology products. The study relied on a descriptive and analytical approach. A comprehensive questionnaire was developed that included the four dimensions of neuromarketing and distributed to a sample of (300) male and female students from various departments at the Northern Technical University in Nineveh Governorate. The data were analyzed using a number of statistical methods, relying on the SPSS V.26 software package, to test the relationships between the independent variables (neuromarketing dimensions) and the dependent variable (wearable technology products). The research results showed significant effects of most neuromarketing dimensions on students' behavior and attitudes toward purchasing wearable technology products, particularly the "targeted advertising" and "product satisfaction" dimensions. This reflects the importance of understanding psychological and neural stimuli in designing modern marketing strategies. This leads us to a set of proposals that focus on developing neuromarketing dimensions and enhancing awareness of wearable technology products within universities to provide students with opportunities to explore them. Furthermore, companies producing these technologies should rely on neuromarketing tools in designing advertising campaigns, given their effective role in influencing consumer behavior.
Keywords: Neuromarketing; Wearable Technology Products; Wearable Technology; Northern Technical University